A 16‐year investigation of legacy phosphorus discharge from Prairie Wolf Slough: a wetland restored on a former farmed field. Issue 3 (14th March 2021) - Montgomery, James A.; Eames, James M.; Klimas, Christie
Abstract : Phosphorus (P) release to surface and groundwater often occurs in wetlands that were restored on former agricultural fields. We identified pore water, shallow groundwater, and plant biomass decomposition as sources of soluble reactive (SRP) and total phosphorus (TP) export to the Chicago River between 1998 and 2014 from Prairie Wolf Slough Wetland Demonstration Project (PWS), a wetland restored on a former farmed field in suburban Chicago, Illinois. We estimated the relative annual contributions of SRP from these sources to yearly discharge to the river and conducted an SRP mass balance. SRP and TP concentrations and loadings were consistently greater at the outlet compared to the inlet, suggesting PWS was a source of P. Twenty‐three grams of SRP was exported during the mass balance study. SRP concentration at the inlet accounted for less than 3% of the SRP exported annually at the outlet to the Chicago River. Plant biomass decomposition, pore water diffusion, and groundwater seepage together accounted for 85% of annual export. Twelve percent of annual SRP export remains unknown. PWS was ineffective in reducing P export, indicating an ecosystem disservice. Our study highlights the need to identify the sources of P exported from wetlands restored on farm fields to better understand the biogeochemical processes that determine whether a wetland will serve as a source or sink of P. Pre‐restoration measurement, followed by decadal‐scale post‐restoration monitoring, of source‐water and soil P are needed to evaluate the success of wetland restorations designed to sequester P from runoff.